STRATEGI PEMROGRAMAN ARSITEKTUR REGENERATIF PADA KAMPUNG APUNG: INTEGRASI RUANG AKUAPONIK DAN KOMUNAL - Giovanny Josefina Limuel; Olga Nauli Komala (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2026)
Kampung Apung in Kapuk, Cengkareng, West Jakarta, is a residential area affected by permanent flooding that has led to environmental degradation, limited communal space, and a decline in residents’ quality of life. These conditions have created an unhealthy living environment with restricted accessibility and inadequate public space. This study aims to formulate a regenerative architectural spatial program through the integration of communal spaces and aquaponics systems to support ecological recovery and strengthen social and economic interactions within the community. The research employs a descriptive qualitative approach through literature review and field observation to examine the relationship between residents’ daily activities, ecological conditions, and the potential of water-based productive spaces. The findings indicate that everyday activities such as social interaction, informal trading, worship, and the use of waterfront areas form dynamic social patterns that naturally generate shared spaces despite the physical limitations of the settlement. Based on these findings, the proposed strategy focuses on providing multifunctional communal spaces that can accommodate social and productive activities simultaneously. The aquaponics system is integrated as an ecological component as well as a medium for community-based economic and educational activities. Through the reciprocal relationship between communal spaces and productive systems, the programming is expected to improve environmental quality while reinforcing social cohesion and the collective identity of Kampung Apung. Keywords:  Aquaponic; Communal; Degradation; Kampung Apung; Regenerative Abstrak Kampung Apung di Kapuk, Cengkareng, Jakarta Barat, merupakan kawasan permukiman yang mengalami degradasi lingkungan, keterbatasan ruang komunal, serta penurunan kualitas hidup masyarakat akibat genangan air permanen. Kondisi tersebut menjadikan lingkungan hunian tidak sehat, sulit diakses, dan minim ruang publik yang layak. Penelitian ini bertujuan merumuskan program ruang dengan arsitektur regeneratif melalui integrasi ruang komunal dan sistem akuaponik sebagai upaya pemulihan ekologis sekaligus penguatan interaksi sosial dan ekonomi warga. Metode penelitian menggunakan pendekatan kualitatif deskriptif melalui studi literatur dan observasi lapangan untuk mengkaji hubungan antara aktivitas keseharian masyarakat, kondisi ekologis, dan potensi ruang produktif berbasis air. Hasil pengamatan menunjukkan bahwa aktivitas berinteraksi, berdagang, beribadah, serta memanfaatkan tepian air membentuk pola sosial yang dinamis dan menjadi dasar terbentuknya ruang bersama meskipun dalam keterbatasan fisik kampung. Berdasarkan temuan tersebut, perancangan diarahkan pada penyediaan ruang komunal multifungsi yang mampu menampung aktivitas sosial dan produktif secara bersamaan. Sistem akuaponik diintegrasikan sebagai elemen ekologis sekaligus sarana ekonomi dan edukasi masyarakat. Melalui hubungan timbal balik antara ruang komunal dan sistem produktif, pemrograman diharapkan dapat memperbaiki kualitas lingkungan serta memperkuat kebersamaan dan identitas sosial Kampung Apung.